2017
DOI: 10.1177/2158244017697164
|View full text |Cite
|
Sign up to set email alerts
|

Group Practice of the Transcendental Meditation® and TM-Sidhi® Program and Reductions in Infant Mortality and Drug-Related Death

Abstract: These two studies tested the prediction that the group practice of a procedure for the development of consciousness, the Transcendental Meditation and TM-Sidhi program, by a sufficiently large group of individuals would be sufficient to reduce collective stress in the larger population, reflected in two stress-related health indicators, infant mortality rate and drugrelated fatality rate. Based on theoretical prediction and prior research, from January 2007 through 2010 (intervention period), this effect shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…Using segmented-trend (linear-spline) regression modeling, these four papers investigated changes in monthly trends of homicide rates and trends in other fatality rates during 2007-2010 as compared with a baseline period November 2002-December 2006. Reported results include reduced trends in U.S. homicide rates, t(84) = -10.17, p < 0.001, f = -1.11; reduced murder and violent crime rate trends in large urban areas, t(83) = -6.14, p < 0.001, f = -0.674 (Dillbeck & Cavanaugh, 2016;Cavanaugh & Dillbeck, 2017a); reduced trend of motor vehicle fatality rates, t(87) = -8.55, p < 0.001, f = -0.917 and fatality rates due to other accidents, t(86) = -3.82, p < 0.001, f = -0.412 (Cavanaugh & Dillbeck, 2017b); and reduction of trend in rates of drug-related fatalities, t(86) = -4.16, p < 0.001, f = -0.449 and U.S. infant mortality, t(87) = -4.50, p < 0.001, f = -0.482 (Dillbeck & Cavanaugh, 2017). Moreover, a pilot study using annual data replicated the reduction of homicide-rate trends during the experimental period and also found that homicide-rate trends rose again when the size of the meditation group fell (Orme-Johnson, 2017; Orme-Johnson et al, in review).…”
Section: Prior Research On the Current Us Social Experimentsmentioning
confidence: 99%
“…Using segmented-trend (linear-spline) regression modeling, these four papers investigated changes in monthly trends of homicide rates and trends in other fatality rates during 2007-2010 as compared with a baseline period November 2002-December 2006. Reported results include reduced trends in U.S. homicide rates, t(84) = -10.17, p < 0.001, f = -1.11; reduced murder and violent crime rate trends in large urban areas, t(83) = -6.14, p < 0.001, f = -0.674 (Dillbeck & Cavanaugh, 2016;Cavanaugh & Dillbeck, 2017a); reduced trend of motor vehicle fatality rates, t(87) = -8.55, p < 0.001, f = -0.917 and fatality rates due to other accidents, t(86) = -3.82, p < 0.001, f = -0.412 (Cavanaugh & Dillbeck, 2017b); and reduction of trend in rates of drug-related fatalities, t(86) = -4.16, p < 0.001, f = -0.449 and U.S. infant mortality, t(87) = -4.50, p < 0.001, f = -0.482 (Dillbeck & Cavanaugh, 2017). Moreover, a pilot study using annual data replicated the reduction of homicide-rate trends during the experimental period and also found that homicide-rate trends rose again when the size of the meditation group fell (Orme-Johnson, 2017; Orme-Johnson et al, in review).…”
Section: Prior Research On the Current Us Social Experimentsmentioning
confidence: 99%
“…The purpose of the empirical aspect of the current paper is to replicate and extend the previous study of drug-related fatality trends 2002–2010 described in Section 2.6 [ 13 ]. The current empirical analysis employs segmented-trend regression modeling, a form of interrupted time series analysis, to test the two research hypotheses described below.…”
Section: Methodsmentioning
confidence: 88%
“…Also included are possible level shifts (intercept changes) between segments. Segmented-trend regression models were employed in six previous peer-reviewed studies of this social experiment [ 13 , 44 , 63 , 64 , 65 , 70 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations